Current and prospective analysis of physician supply and demand in Peru for years 2005-2011 - Carrasco Cortez, Víctor (2008)
Introduction: There is oversupply in pre-graduate formation of human resources for health care. The average number of newly formed physicians went from 27 in the 1917-1926 period to 1026 per year during 1990-1995, and a further increase has been reported, e.g., from 1287 in 1998 to 2183 in 2003. The Peruvian College of Physicians is concerned about a risk for reduced quality in the deliverance of health care services to the community and to the individuals because of an oversupply of health care professionals with heterogeneous schooling standards, and another contributing factor is an inadequate distribution and a quite variable professional competence of physicians in Peru.Objective: To identify the number and distribution of physicians in Peru, their working status, and the relationship between general practitioners and specialized physicians, describing all the aspects of supply and demand.Material and Methods: Observational, descriptive, analytical, prospective and cross-sectional study with three components: descriptive, exploratory, and prospective.Results: There is a significant increase in the number of physicians graduating from medical schools. According to the projection rate calculated on the basis of the figures for the last five years (2.8% from public medical schools and 12.7% from private medical schools), we had 2156 graduate medical students in 2005, and this figure may rise up to 3218 in year 2011. The current supply of general practitioners is 25935 professionals, for an estimated demand in 16196, so there is a 9739 oversupply of physicians. There is also a 1611 oversupply of specialized physicians.Conclusion: It is advisable, on the basis of the described situation, to take urgent measures in order to halt physician oversupply: temporally withdraw the creation of new medical schools for the next five years, establish a specialized group for analyzing additional measures aiming to regulate medical schools supply. It is also necessary to enhance residence training towards basic specialties: obstetrics and gynecology, pediatrics, internal medicine, and general surgery.